2020
DOI: 10.3390/molecules25225366
|View full text |Cite
|
Sign up to set email alerts
|

Functionality of Cricket and Mealworm Hydrolysates Generated after Pretreatment of Meals with High Hydrostatic Pressures

Abstract: The low consumer acceptance to entomophagy in Western society remains the strongest barrier of this practice, despite these numerous advantages. More positively, it was demonstrated that the attractiveness of edible insects can be enhanced by the use of insect ingredients. Currently, insect ingredients are mainly used as filler agents due to their poor functional properties. Nevertheless, new research on insect ingredient functionalities is emerging to overcome these issues. Recently, high hydrostatic pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 91 publications
(179 reference statements)
3
8
1
1
Order By: Relevance
“…The solubility of protein hydrolysates improved. The emulsifying and foaming characteristics exhibited better functional properties, which indicates that cricket protein has potential to be a component of designed food and functional food, which is also reported by other authors [ 51 , 52 , 53 ].…”
Section: Description Of Selected Insectssupporting
confidence: 81%
“…The solubility of protein hydrolysates improved. The emulsifying and foaming characteristics exhibited better functional properties, which indicates that cricket protein has potential to be a component of designed food and functional food, which is also reported by other authors [ 51 , 52 , 53 ].…”
Section: Description Of Selected Insectssupporting
confidence: 81%
“…Some industrial processes affecting proteins may even improve protein techno-functionalities. Heat treatment, enzymatic hydrolysis, ultrasound, and more recently, high hydrostatic pressure (HHP) have been reported to improve foam capacity, solubility, water-holding capacity, and other desirable qualities [ 9 , 10 , 11 ]. More specifically, HHP is a nonthermal process that applies isostatic pressure (up to 1000 MPa), inducing the destabilization of noncovalent bonds (hydrophobic, hydrogen, and ionic bonds) within the protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…Protein solubility, foam properties, emulsifying activity, and oil-binding capacity increased with a decrease in the protein molecular weight (decrease from 25−75 kDa to 10−15 kDa) after enzymatic hydrolysis. However, Dion-Poulin et al (2020) found no significant difference in protein functionality following enzymatic hydrolysis by Alcalase ® (3%, 80°C, 15 min) but reported that emulsifying activity decreased. Mintah et al.…”
Section: Quality Characteristics Of the Protein In Processed Edible I...mentioning
confidence: 89%